Friction vs.

JP7636412B2Active Publication Date: 2025-02-26NISSHINBO BRAKE INC
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2022531710
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-16
Filing Date
2021-06-09
Publication Date
2025-02-26
Estimated Expiration
2041-06-09

AI Technical Summary

Benefits of technology

【0022】 本発明によれば、結合材、繊維基材、摩擦調整材を含有し、銅成分及び鉄系金属繊維を含有しない摩擦材組成物から成る摩擦材を具備するディスクブレーキパッドと、ステンレス鋼製のディスクロータから成る摩擦対において、優れた低速域の効力安定性を有する摩擦対を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636412000001
    Figure 0007636412000001
  • Figure 0007636412000002
    Figure 0007636412000002
  • Figure 0007636412000003
    Figure 0007636412000003
Patent Text Reader

Abstract

[Problem] To provide a friction pair formed from a stainless steel disc rotor, and a disc brake pad that is equipped with a friction material formed from a friction material composition containing a bonding material, a fiber base material and a friction adjustment material, but not containing a copper component or iron-based metal fibers, said friction pair achieving excellent and stable effectiveness at low speeds. [Solution] The present invention uses a friction material composition containing 20-30 wt% of a titanate serving as an inorganic friction adjustment material with respect to the total friction material composition amount, but not containing mica or vermiculite. Said titanate is preferably lithium potassium titanium oxide having a layered crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to friction pairs, and more particularly to friction pairs for use in vehicles such as passenger cars. [Background technology]

[0002] 2. Description of the Related Art Conventionally, disc brake pads having a friction material attached to a metal base member have been used as friction members for disc brakes in passenger vehicles.

[0003] In recent years, there has been a demand for quieter brakes, and so disc brake pads using a friction material called NAO material, which produces less brake noise, have come into widespread use.

[0004] The NAO friction material is a material obtained by molding a friction material composition containing a binder, a fiber base material other than steel-based fibers such as steel fibers or stainless steel fibers, and a friction modifier, and is classified as a friction material along with semi-metallic friction materials and low-steel friction materials that contain steel-based fibers as a fiber base material. In recent years, due to legal restrictions on the copper content in the United States, the development of friction materials that contain only 5% by weight or less of copper or that do not contain any copper at all has become common.

[0005] Patent Document 1 describes a friction material composition containing a fibrous base material, a friction modifier, and a binder, in which the copper content in the friction material composition is 0.5 mass % or less in terms of elemental copper, and the friction material composition contains granular titanate as the friction modifier, in which titanate is made into granules, and the average particle size of the granular titanate is 100 to 250 μm, and a friction material obtained by molding the friction material composition.

[0006] Patent Document 2 describes a friction material composition that contains a fiber base material, an inorganic filler, an organic filler, and a binder, and has a copper content of 0.5 mass % or less, in which the inorganic filler includes an abrasive having an average particle diameter of 3 to 5 μm and an abrasive having an average particle diameter of 9 to 13 μm, and the inorganic filler includes a titanate having an average particle diameter of 1.5 to 4.5 μm and a titanate having an average particle diameter of 15 to 45 μm.

[0007] As a mating material for disc brake pads equipped with such friction materials containing almost no copper components, disc rotors made of cast iron are used as described in Patent Document 3. Such cast iron disc rotors have a problem of low corrosion resistance and rusting during use, and a countermeasure has been required on the friction material side.

[0008] For example, Patent Document 4 discloses a friction material containing a binder, a friction modifier, and a fibrous base material, which does not contain a copper component and contains 10 to 20 volume % of at least one type of titanate compound having a plurality of convex shapes and 1 to 20 volume % of biosoluble inorganic fibers, thereby improving rust removal properties of a mating material.

[0009] However, as the use of regenerative brakes increases with the spread of electric and hybrid vehicles, the braking load on the friction material of conventional hydraulic brakes is reduced, resulting in a problem that sufficient rust removal properties cannot be obtained even when using technology such as that described in Patent Document 4.

[0010] Therefore, disk rotors made of stainless steel, which has excellent rust resistance, have come to be used.

[0011] Patent Document 5 discloses a four-wheel disk rotor manufactured from a stainless steel plate having a martensite structure or a mixed structure of a martensite phase and a ferrite phase.

[0012] Patent Document 6 describes a disk rotor for automobiles having a structure including martensite and carbonitrides, and optionally including ferrite.

[0013] Patent Document 7 describes the following composition by mass: C: 0.005-0.100%, Si: 0.01-1.00%, Mn: 0.010-3.00%, P: 0.040% or less, S: 0.0100% or less, Cr: 10.0-14.0%, N: 0.005-0.100%, V: 0.03-0.30%, Al: 0.001-0.050%, B: 0.0002-0.0050%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0-1.00%, Ti: 0-0.40%, N b: 0-0.40%, Zr: 0-0.40%, Co: 0-0.400%, Sn: 0-0.40%, REM: 0-0.050% or less, Mg: 0-0.0100%, Ca: 0-0.0100%, Sb: 0-0.50%, Ta: 0-0.3000%, Hf: 0-0.3000%, Ga: 0-0.1000%, the balance being Fe and impurities, the metal structure being a ferrite phase, and carbonitrides having a circle-equivalent diameter of 0.3 μm or more are present in an arbitrary cross section at 10-50 pieces / 100 μm 2 The present invention describes a disk rotor for an automobile, which is made of a stainless steel plate and is characterized by the presence of

[0014] In light of this background, there is a demand for a friction material made of a friction material composition that does not contain copper components and that is compatible with stainless steel disc rotors, which have excellent rust resistance. However, it has become clear that when a friction material that does not contain copper components, which has been used in combination with conventional cast iron disc rotors, is applied to a disc brake equipped with a stainless steel disc rotor, the effectiveness stability at low speeds is significantly reduced. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] JP 2017-57312 A [Patent Document 2] JP 2018-162385 A [Patent Document 3] Japanese Patent Application Publication No. 2-134425 [Patent Document 4] JP 2017-149971 A [Patent Document 5] JP 2016-117925 A [Patent Document 6] JP 2019-173086 A [Patent Document 7] JP 2019-178419 A Summary of the Invention [Problem to be solved by the invention]

[0016] The present invention aims to provide a friction pair having excellent effectiveness stability in a low speed range, the friction pair being composed of a disc brake pad having a friction material made of a friction material composition containing a binder, a fiber base material, and a friction modifier, but not containing a copper component or iron-based metal fibers, and a stainless steel disc rotor. [Means for solving the problem]

[0017] As a result of extensive investigations, the present inventors have discovered that in a friction pair consisting of a disc brake pad equipped with a friction material made of a friction material composition that contains a binder, a fibrous base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor, a friction material composition containing a specific amount of titanate as a friction modifier and using a friction material composition that does not contain mica or vermiculite, a friction pair having excellent effectiveness stability in the low speed range can be obtained, and have completed the present invention.

[0018] The present invention relates to a friction pair consisting of a disc brake pad having a friction material made of a friction material composition containing a binder, a fiber base material, and a friction modifier, but not containing a copper component or iron-based metal fibers, and a stainless steel disc rotor, and is based on the following technology.

[0019] (1) A friction pair consisting of a disc brake pad having a friction material made of a friction material composition containing a binder, a fiber base material, and a friction modifier, but not containing a copper component or iron-based metal fiber, and a stainless steel disc rotor, wherein the friction material composition contains 20 to 30% by weight of titanate as an inorganic friction modifier based on the total weight of the friction material composition, and does not contain mica or vermiculite.

[0020] (2) The friction pair according to (1), wherein the titanate has a layered crystal structure.

[0021] (3) The friction pair according to (1), wherein the titanate is lithium potassium titanate. Effect of the Invention

[0022] According to the present invention, there can be provided a friction pair having excellent effectiveness stability in a low speed range, the friction pair being composed of a disc brake pad having a friction material made of a friction material composition that contains a binder, a fiber base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In conventionally used cast iron disc rotors, a relatively large amount of titanate is added to the friction material composition in combination with mica or vermiculite to uniformly control the thickness of the coating, thereby stabilizing the effectiveness at low speeds.

[0024] In contrast, in stainless steel disc rotors, it was revealed that the addition of mica or vermiculite, which are essential components for controlling the thickness of the titanate transfer coating and have a Mohs hardness of 4 or less and are cleavable, inhibits the formation of the titanate transfer coating, making it impossible to obtain good effectiveness stability at low speeds. These are friction materials used in cast iron disc rotors.

[0025] In the present invention, a friction pair is provided, which is a disc brake pad having a friction material made of a friction material composition that contains a binder, a fiber base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor. The friction material composition contains 20 to 30% by weight of titanate as an inorganic friction modifier based on the total amount of the friction material composition, and does not contain mica or vermiculite.

[0026] By adding titanate as a friction modifier in an amount of 20 to 30% by weight based on the total amount of the friction material composition, a coating of an appropriate thickness can be formed on the surface of the stainless steel disc rotor.

[0027] As the titanate, one or a combination of two or more of titanates having a tunnel crystal structure, such as potassium hexatitanate, potassium octatitanate, and sodium hexatitanate, and titanates having a layered crystal structure, such as lithium potassium titanate and magnesium potassium titanate, can be used.

[0028] Among these, in terms of structure, it is preferable to use titanates having a layered crystal structure, and in terms of composition, it is preferable to use magnesium potassium titanate alone.

[0029] The shape of the titanate may be columnar, plate-like, particulate, scaly, or irregular having a plurality of protrusions.

[0030] Furthermore, since the friction material composition does not contain mica or vermiculite, which have a Mohs hardness of 4 or less and cleavage properties and are essential components of friction material compositions that do not contain copper components or iron-based metals and are used in conventional cast iron disc rotors, the formation of a titanate transfer coating is not inhibited, and good effectiveness and stability can be obtained at low speeds.

[0031] Examples of mica that is not contained in the friction material composition include phlogopite, muscovite, and sericite.

[0032] In the present invention, the Mohs hardness is the old Mohs hardness scale represented as "1. talc, 2. gypsum, 3. calcite, 4. fluorite, 5. apatite, 6. orthoclase, 7. quartz, 8. topaz, 9. corundum, 10. diamond."

[0033] <Friction material composition> The friction material used in the friction pair of the present invention is made of a friction material composition containing, in addition to the titanate, a binder, a fibrous base material, and a friction modifier that are usually used in friction materials.

[0034] Examples of the binder include binders that are commonly used in friction materials, such as straight phenol resin, acrylic rubber modified phenol resin, silicone rubber modified phenol resin, nitrile rubber modified phenol resin, cashew oil modified phenol resin, aralkyl modified phenol resin (phenol aralkyl resin) obtained by reacting phenols, aralkyl ethers, and aldehydes, acrylic rubber dispersed phenol resin, silicone rubber dispersed phenol resin, and fluoropolymer dispersed phenol resin. These may be used alone or in combination of two or more.

[0035] The content of the binder is preferably 4 to 9% by weight, and more preferably 6 to 8% by weight, based on the total amount of the friction material composition.

[0036] Examples of the fiber base material include organic fibers that are commonly used in friction materials, such as aramid fibers, acrylic fibers, cellulose fibers, and poly-paraphenylene benzobisoxazole fibers. These may be used alone or in combination of two or more.

[0037] The content of the fibrous base material is preferably 1 to 5% by weight, and more preferably 2 to 4% by weight, based on the total amount of the friction material composition.

[0038] As the friction modifier, a lubricant, an inorganic friction modifier, or an organic friction modifier can be used.

[0039] Examples of lubricants include carbonaceous lubricants such as artificial graphite, natural graphite, crushed graphite sheet powder, petroleum coke, coal coke, elastic graphitized carbon, and crushed polyacrylonitrile oxide fiber powder, and metal sulfide lubricants such as tin sulfide, molybdenum disulfide, iron sulfide, bismuth sulfide, zinc sulfide, and composite metal sulfides. These may be used alone or in combination of two or more.

[0040] The content of the lubricant is preferably 10 to 18% by weight, and more preferably 11 to 16% by weight, based on the total amount of the friction material composition.

[0041] In addition to the titanates described above, examples of inorganic friction modifiers include calcium hydroxide, calcium carbonate, barium sulfate, talc, dolomite, zeolite, iron oxide, manganese oxide, calcium silicate hydrate, magnesium oxide, silicon dioxide, zirconium oxide, zirconium silicate, γ-alumina, α-alumina, silicon carbide, wollastonite, sepiolite, basalt fiber, glass fiber, biosoluble ceramic fiber, rock wool, and the like. These may be used alone or in combination of two or more.

[0042] The content of the inorganic friction modifier, including the titanate, is preferably 60 to 82% by weight, and more preferably 65 to 76% by weight, based on the total amount of the friction material composition.

[0043] Examples of the organic friction modifier include cashew dust, ground tire tread rubber powder, polytetrafluoroethylene powder, and organic friction modifiers that are commonly used in friction materials, such as vulcanized or unvulcanized rubber powders, such as acrylic rubber, isoprene rubber, nitrile butadiene rubber, styrene butadiene rubber, butyl rubber, and silicone rubber. These may be used alone or in combination of two or more.

[0044] The content of the organic friction modifier is preferably 3 to 8% by weight, and more preferably 5 to 7% by weight, based on the total amount of the friction material composition.

[0045] <Method of manufacturing disc brake pads> The disc brake pad according to the present invention typically comprises: A mixing step of uniformly mixing the friction material composition (friction material raw material) in a predetermined amount using a mixer to obtain a friction material raw material mixture; A heat and pressure molding process in which the obtained friction material raw material mixture is layered on a back plate that has been separately washed, surface-treated, and coated with an adhesive, and then the layered mixture is placed in a thermoforming mold and heated and pressurized to form the mixture. a heat treatment step in which the obtained molded product is heated to complete the curing reaction of the binder; Painting process, where paint is applied by spray painting or electrostatic powder coating; The paint baking process involves baking the paint. A polishing process to form a friction surface using a rotating grindstone; It is manufactured through the process.

[0046] In some cases, the manufacturing process may be carried out in the following order after the heat and pressure molding process: painting, a heat treatment process which also serves as painting baking, and a polishing process.

[0047] If necessary, before the heat and pressure molding process, a granulation step of granulating the friction material raw material mixture; A kneading step of kneading the friction material raw material mixture; a preforming step in which the friction material raw material mixture or the granulated product obtained in the granulating step and the kneaded product obtained in the kneading step are charged into a preforming mold to form a preforming product; may be carried out, and a scorching step may be carried out after the hot-press molding step.

[0048] <Stainless steel disc rotor> As the stainless steel disc rotor, for example, a martensitic stainless steel disc rotor or a ferritic stainless steel disc rotor can be used. EXAMPLES

[0049] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0050] [Method of manufacturing friction materials of Examples 1 to 7 and Comparative Examples 1 to 3] The friction material composition shown in Table 1 was charged into a Lödige mixer and mixed for 5 minutes to obtain a friction composition mixture. This friction material composition mixture was pressed in a molding die at 30 MPa for 10 seconds to obtain a friction material preform. This friction material preform was placed on a steel back plate that had been previously cleaned, surface-treated, and coated with an adhesive, and molded in a thermoforming die at a molding temperature of 150°C and a molding pressure of 40 MPa for 10 minutes to obtain a friction material molded product. This friction material molded product was heat-treated (post-cured) for 5 hours at 200°C, and then polished to form a friction surface, to produce a passenger car disc brake pad.

[0051] [Table 1]

[0052] Furthermore, the friction material of the disc brake pad was cut into a size of 25 mm×15 mm×15 mm to obtain test pieces of Examples 1-7 and Comparative Examples 1-3.

[0053] Table 2 shows the test conditions, mating material, evaluation items, and evaluation criteria used to verify the low-speed force stability using these test pieces.

[0054] [Table 2]

[0055] Table 3 shows the evaluation results of the "low speed range effectiveness stability" shown in Table 2 for each of the examples and comparative examples.

[0056] [Table 3]

[0057] From Table 3, it can be seen that the friction material satisfying the conditions of the present invention has good effectiveness stability in the low speed range. [Industrial Applicability]

[0058] According to the present invention, in a friction pair consisting of a disc brake pad having a friction material made of a friction material composition containing a binder, a fiber base material, and a friction modifier, but not containing a copper component or iron-based metal fibers, and a stainless steel disc rotor, it is possible to provide a friction pair having excellent effectiveness stability in a low speed range, which is of extremely high practical value.

Claims

1. The binder is 6 to 8% by weight based on the total amount of the friction material composition. A fiber base material is 2 to 4% by weight based on the total amount of the friction material composition. A lubricant is contained in an amount of 11 to 16% by weight based on the total amount of the friction material composition. As a friction modifier, an inorganic friction modifier is used in an amount of 65 to 76% by weight based on the total amount of the friction material composition, An organic friction modifier is contained in an amount of 5 to 7% by weight based on the total amount of the friction material composition. The friction pair is composed of a disc brake pad having a friction material made of a friction material composition containing no copper component and no iron-based metal fibers, and a stainless steel disc rotor, the friction material composition containing 20 to 30% by weight of a titanate having a layered crystal structure as an inorganic friction modifier based on the total weight of the friction material composition, and not containing mica or vermiculite as inorganic friction modifiers.

2. 2. The friction pair according to claim 1, wherein the titanate is lithium potassium titanate.

Citation Information

Patent Citations

  • Semiconductor device for picking up image

    JP1987081755A

  • Disk rotor material

    JP1990134425A

  • Friction material

    JP2000265157A

  • Flow improver for biodiesel fuel oil

    JP2011241382A

  • Friction material

    JP2013076058A